Diagnosis and treatment of liver injuries in blunt abdominal injury using minimally invasive technologies - Ya. V. Gavrishchuk; V. A. Manukovsky; A. N. Tulupov; A. E. Demko; E. A. Kolchanov; V. E. Savello; M. N. Pravosud (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to improve the treatment of victims with liver injury in blunt abdominal trauma by using minimally invasive methods of diagnosis and treatment.  METHODS AND MATERIALS. We analyzed the treatment results of 76 patients with blunt liver injuries using traditional treatment and 78 patients who were treated with the developed new algorithm. In the second group, patients with ultrasound signs of liver injuries and stable hemodynamics (BP>90 mm Hg) underwent MSCT with intravenous contrast. In the absence of ongoing bleeding signs, conservative treatment was carried out; if they were detected, angiography with selective angioembolization was performed.  RESULTS. There were no statistically significant differences in gender, age, mechanism and severity of injury (according to the ISS, Tsibin, VPH-P scales) and severity of the condition (VPH-SP) between the patients of the groups. More than half (52.3 %) of the victims of the main group were treated without abdominal surgery. By using the proposed algorithm in patients with stable hemodynamics, laparocentesis gave way to less traumatic and more accurate methods of diagnosing intra-abdominal bleedings. All laparotomies in the main group were performed for other abdominal injuries. In the victims of both groups, video laparoscopy was diagnostic in nature. One patient of the main group with liver injury of IV degree according to the AAST scale with ongoing intraparenchymatous and intraperitoneal bleeding underwent endovascular hemostasis.  CONCLUSION. The use of non-operative and minimally invasive treatment of hemodynamically stable patients with liver ruptures in isolated and combined blunt abdominal trauma allowed to reduce the number of the performed diagnostic video laparoscopies by 24 %, laparotomies by 29 %, and completely abandon laparocentesis as a diagnostic method, reduce mortality rate by 4.6% and the duration of inpatient treatment of surviving patients for 4 days.